Pomen vzajemnega kataloga za oblikovanje enotnega KIS - Martelanc, Tomo (Knjižnica, 1988)
Shared catalogue as an element of library and information system automation. Cooperation between Yugoslav national libraries on the field of the elaboration of Yugoslav shared catalogue. Principles of cooperation, work sharing, rights and obligations, connected with shared cataloging. Shared catalogue as an important means for user's work in libraries. Incorporation and work on shared catalogue and education for searching in it.
Keywords: Jugoslavija; Yugoslavia; vzajemni katalogi; knjižnični informacijski sistemi